2016
DOI: 10.1080/2162402x.2016.1250992
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of low-dose interleukin-2 and the clinical outcomes of hematopoietic stem cell transplantation: A randomized study

Abstract: Leukemia relapse and chronic graft-versus-host disease (cGVHD) are still major obstacles of allogeneic hematopoietic stem cell transplantation (allo-HSCT). The numbers and activity of natural killer (NK) and Tregulatory cells can be increased post-transplantation by exposure to interleukin-2 (IL-2). We tested whether administering low-dose IL-2 would decrease leukemia relapse while reducing cGVHD after allotransplantation. This controlled, open-label randomized trial included 90 recipients of allotransplants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…Alleviation of the manifestations of chronic GVHD was observed in a substantial proportion of these patients; out of 23 patients, 12 had major responses involving multiple sites (15). Further studies proposed similar regimens for the prevention of GVHD [e.g., s.c. injections of low-dose IL-2 (1 million IU/m 2 ) daily for 14 d, followed by a 14-d hiatus (37), or 0.1-0.2 million IU/m 2 three times per week for days 0-90 (38)]. These findings suggested that the prophylactic administration of lowdose IL-2 could effectively enhance early Treg expansion and suppress acute and chronic GVHD (35,36).…”
Section: Low-dose Il-2 Therapy In Autoimmune Diseasesmentioning
confidence: 95%
“…Alleviation of the manifestations of chronic GVHD was observed in a substantial proportion of these patients; out of 23 patients, 12 had major responses involving multiple sites (15). Further studies proposed similar regimens for the prevention of GVHD [e.g., s.c. injections of low-dose IL-2 (1 million IU/m 2 ) daily for 14 d, followed by a 14-d hiatus (37), or 0.1-0.2 million IU/m 2 three times per week for days 0-90 (38)]. These findings suggested that the prophylactic administration of lowdose IL-2 could effectively enhance early Treg expansion and suppress acute and chronic GVHD (35,36).…”
Section: Low-dose Il-2 Therapy In Autoimmune Diseasesmentioning
confidence: 95%
“…297,309,310 Accumulating evidence suggest indeed that metronomic chemotherapy and hypofractionated radiation (rather than chemotherapy at the MTD and high single-dose radiation) exerts superior immunostimulatory (and hence therapeutic, at least in some settings) effects. [311][312][313][314] Alongside, it will be important to devise highly efficient combinatorial regimens that harness not only the ability of some treatments to drive ICD, but also the off-target immunostimulatory effects of a variety of agents.…”
Section: Discussionmentioning
confidence: 99%
“…Correlative studies demonstrated that circulating Treg and natural killer (NK) cells were increased in the IL-2 cohort during the treatment periods. 76…”
Section: Targeting Cell Surface Receptors For In Vivo Treg Expansionmentioning
confidence: 99%